Sacred Space and Holy War The Politics, Culture and History of Shi`ite Islam - Juan Cole (Tauris & Co Ltd, 2002)
The rise of nation-states during the past two centuries has had a profound effect on the writing of history, which has increasingly been tied to artificial â€œnationalâ€ frameworks. Stories that cannot be fit into the narrative of the rise of the nation have often been neglected by contemporary historians. Worse, some movements with an international aspect have been reconfigured as national or written about mainly as an element in the formation of particular nations. Thus, most writing about the Twelver branch of Shi`ite Islam after about 1500, when it became the official religion of Iran, has focused on Iranian Shi`ism. The history of Shi`ite minorities in Eastern Arabia, and in what is now Pakistan and Lebanon, was relatively neglected by historians until recently, and of all non-Iranian Twelver communities only those of India and Iraq have been treated at length in contemporary English-language scholarship (and this only during the past decade and a half). Yet, recovering the history of this important branch of Islam in these particular nations is only part of the task that historians must set themselves. Looking at Shi`ite Islam (and other major Islamic movements) outside the box of a national framework, at its international networks and the profound interactions they entail, is among the prime tasks of historians of religion. One historian has spoken of rescuing Chinese history from the nation.1 I propose that we need to rescue Shi`ite Islam from the nation. Accordingly, this book has no national focus. It is concerned with intellectual and social developments among Arabic-speaking, Persian-speaking, and Urdu-speaking Shi`ites. It examines three arenas of Shi`ite activity, the Arab world, Iran and South Asia (India and later Pakistan) synoptically. That is, I try to keep the interactions between the three consistently in view. One of my readers once spoke of the â€œvertigoâ€ induced by my alternation between Najaf in what is now Iraq and Lucknow in India, between Manama in Bahrain and Shiraz in Iran. I would argue in reply that this vertigo is a feeling induced by our habit of thinking within â€œnationalâ€ categories, categories that are anachronistic if imported into the Middle East and South Asia before the 2 SACRED SPACE AND HOLY WAR twentieth century, and which obscure important developments even later on. The interaction of early modern and modern Iranian Shi`ism with its neighbors and even further afield has been much greater than is usually recognized. It was a commonplace of an earlier generation of historians that when Iranâ€™s rulers promulgated the Shi`ite branch of Islam in the sixteenth century, it threw up a barrier to communication and trade between the Sunni east and west of the Islamic world. This thesis has the disadvantage of being untrue. It has the additional disadvantage of obscuring the ways in which Iran - throughout the Safavid (1501-1722), Qajar (1785-1925), Pahlevi (1926-1979) and Khomeinist eras - has continued to export and influence religious movements far beyond its borders. Shi`ite Iran was not a bulkhead but a fluid field of interaction, subject to outside influences but also sending tributaries abroad. Iranian Shi`ism exercised a profound influence in these centuries on many regions of the Arab East, South Asia, and Central Asia. This book looks at developments from 1500 to the present, though most chapters deal with the less-studied period before the twentieth century, and with the relatively little-studied Indian and Arab communities and their interactions with Iranian currents. What were the dynamics that allowed newly Shi`ite Iran under the Safavids to exercise religious influence over Iranâ€™s neighbors? What were the international implications of the turmoil in Iran of the eighteenth century, and then the restoration of state support for Shi`ism under the Qajars? What was the impact on the religion of the age of colonialism from the eighteenth to the early twentieth centuries? How did the â€œhigh modernistâ€ state-building project of the Pahlevis affect the â€œShi`ite International?â€ Finally, how have political Shi`ism and the Khomeinist revolution affected other Shi`ite communities? How did the state structures, political economies and communications networks of each of these eras affect the influences Iranians could bring to bear? I want to underline that I do not see adherence to Shi`ism as a primordial identity, but rather as a socially constructed one into which individuals are mobilized in every generation or which they adopt for their own reasons. Shi`ites born into the faith have converted out of it to Sunnism, Christianity, the Baha'i faith, secularism, and Marxism. Converts hailing from Sunnism, Hinduism, Judaism, and Christianity have adopted it. Observers once tended to see Twelver Shi`ism as a stagnant tradition mired in rigidity, but the surprise of the new academic literature on it is that Shi`ism has arguably been growing significantly not only in the past five hundred years but in the past two hundred. The Shi`ite majority of Iraq (where they are estimated to be 55 percent of the population) results in large part from the conversion of Arab tribes in the south to this branch of Islam in the course of the nineteenth century.